Responsive teaching in science and mathematics - Robertson, Amy D. 1984-; Scherr, Rachel E.; Hammer, David (New York Routledge, 2016)
Answering calls in recent reform documents to shape instruction in response to students' ideas while integrating key concepts and scientific and/or mathematical practices, this text presents the concept of responsive teaching, synthesizes existing research, and examines implications for both research and teaching. Case studies across the curriculum from elementary school through adult education illustrate the variety of forms this approach to instruction and learning can take, what is common among them, and how teachers and students experience it. The cases include intellectual products of students' work in responsive classrooms and address assessment methods and issues. Many of the cases are supplemented with online resources (http://www.studentsthinking.org/rtsm) including classroom video and extensive transcripts, providing readers with additional opportunities to immerse themselves in responsive classrooms and to see for themselves what these environments look and feel like.
Preface -- Chapter 1: What is responsive teaching? / Amy D. Robertson, Leslie J. Atkins, Daniel M. Levin, and Jennifer Richards -- Chapter 2: A review of the research on responsive teaching in science and mathematics / Jennifer Richards and Amy D. Robertson -- Chapter 3: Examining the products of responsive inquiry / Leslie J. Atkins and Brian W. Frank -- Chapter 4: Understanding responsive teaching and curriculum from the students' perspective / Tiffany-Rose Sikorski -- Chapter 5: Navigating the challenges of teaching responsively: An insider's perspective / April Cordero Maskiewicz -- Chapter 6: What teachers notice when they notice student thinking: Teacher-identified purposes for attending to students' mathematical thinking / Adam A. Colestock and Miriam Gamoran Sherin -- Chapter 7: The role subject matter plays in prospective teachers' responsive teaching practices in elementary math and science / Janet E. Coffey and Ann R. Edwards -- Chapter 8: Attending to students' epistemic affect / Lama Z. Jaber -- Chapter 9: Attention to student framing in responsive teaching / Jennifer Radoff and David Hammer -- Chapter 10: Methods to assess teacher responsiveness in situ / Jennifer Evarts Lineback -- Chapter 11: Documenting variability within teacher attention and responsiveness to the substance of student thinking / Amy D. Robertson, Jennifer Richards, Andrew Elby, and Janet Walkoe -- Epilogue / David Hammer -- List of Contributors
Includes bibliographical references and index.
Keywords: Science -- Study and teaching; Mathematics -- Study and teaching